Fertility intention and contraceptive use among males in Nigeria - Oluwaseyi, Adeyoju Temitope (My University, 2013)
Background: Many African countries are still characterized by high fertility rates and low use of modern contraceptives despite numerous reproductive and health programs which aims to increase level of use in these countries. In recent times, there is an increasing body of literature on the role of men in family planning. These studies came about as a result of the inconsistencies observed with women’s inability to match fertility intention to their contraceptive behaviour despite the fact that most family planning programmes have concentrated on women. A potential explanation for this ambivalence is the great influence that male partners exert on women’s contraceptive use and fertility outcome in households. Could fertility intention of males therefore predict their modern contraceptive use in households? This study examined if and how fertility intention of males in Nigeria influences their modern contraceptive use. Methods: This is a cross-sectional study which used data from the Nigerian Demographic and Health Survey 2008. The population of interest in this study are sexually active males (had sex in the last one month before survey) of ages 15-59 interviewed during the survey. The dependent variable is current contraceptive use while the independent variables include demographic, socio-economic and reproductive characteristics of the males. The analysis of data was done at univariate, bivariate and multivariate levels to examine the association between male fertility intention and contraceptive use. Results: Results showed that only 9.0% of the 6,486 males in the study sample were using modern contraceptive methods, 13.1% want no more children and 33.4% want to delay having a/next child after two years while 33.4% want to have a/next child within 2 years. Fertility intention was found to be associated with use of modern contraceptive methods at both bivariate and multivariate levels. Result showed that men who do not want a/another child were significantly more likely (OR= 2.89) to use modern contraceptive method compared to men who wanted a/another child within two years. Men who wanted to space childbirth (want after two years) were also more likely to use modern contraceptive (OR= 1.61) when compared to men who wanted a child within two years. Conclusions: Men who were limiting or spacing child birth have higher propensity to use modern contraceptive method compared to men that wanted another child within two years. This suggests that fertility intention of men in Nigeria has an influence on their contraceptive behaviour and could be a good prediction for fertility outcomes in the country at large.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanties, School of Social Sciences (Demography and Population Studies), 2013